Pengaruh latihan Rondo terhadap keterampilan menyerang pada tim MAN 1 Kota Gorontalo - Diuli, Mohamad Reza Pratama (-, 2025)
The objective of this study is to determine the effect of Rondo training on futsal attacking skills. The research employs an experimental method with a sample of 10 players from MAN 1 Kota Gorontalo. Data collection was conducted using Game Situation tests, analyzed through both descriptive and inferential statistical methods to test the research hypotheses. Based on the t-test data analysis for attacking skills, the observed value (-4.177) with a significance level of 0.002 0.05 indicates that Rondo training has an effect on futsal attacking skills. These results show a significant influence of Rondo training on the attacking skills of the MAN 1 Kota Gorontalo futsal team.